Study on Development and Performance Evaluation of a Maize Roaster - Ilori Titus Adeyinka; Raji Abuduganiyu Olayinka; Adejumo Akinfoye Oyime; Kilanko Oluwaseun (Current Topics in Agricultural Sciences Vol. 6, 2022)
The objective of this study was to develop a maize roaster with treadle drive blower and evaluated its performance using charcoal tray with different pattern of air flow duct. The economic situation in most developing countries have left farmers and processors operating at small scale, hence the use of automated and electric power driven equipment is limited to the few large scale processors. A maize roaster with treadle drive blower was developed, by calculating to specification each machine element, using locally sourced materials and various fabrication techniques. The maize roaster was evaluated for performance by recording time of maize roasting on four charcoal tray with different partner of air flow duct using completely randomize design and Duncan multiple range test. The result of evaluation showed that tray with semicircular pipe shape air flow duct is the most efficient and effective since it has mean time of roasting of 499.83 seconds compare with tray with direct faced shape air flow duct that has mean time of 536.75 seconds, tray with double cone shape air flow duct with mean 553.08 seconds and tray with single cone shape air flow duct which has mean of 694.58 seconds in accordance with Duncan multiple range test as efficiency increases with decrease in mean separation. The machine has demonstrated that it is simple to run and maintain without requiring specific training; consequently, the machine’s performance and compactness will make it acceptable and adaptable to the small or medium scale maize business.